Gas-liquid chromatography of cellular fatty acids for identification of staphylococci. - Stoakes, L (J Clin Microbiol, 1994)
A commercially available, computer-assisted microbial identification system (MIS) employs gas-liquid chromatographic analyses of bacterial fatty acids. The MIS was used to identify 470 isolates of Staphylococcus species. The accuracy of the MIS was compared with the accuracies of conventional methods. There was a complete agreement between the MIS and conventional methods in the identification of 413 (87.8%) strains. For 36 of 45 misidentified strains, the correct identification was listed by the MIS as a choice but not as the first choice. Twelve strains could not be matched. All strains of Staphylococcus cohnii, S. epidermidis, S. intermedius, S. lugdunensis, S. schleiferi, S. sciuri, S. simulans, and S. xylosus were correctly identified. Two species, S. hominis and S. saprophyticus, accounted for 52.6% (30 of 57) of the misidentifications. Seventy-eight organisms were retested. Identification of 73 organisms remained unchanged, and for five organisms, the second choice became first and vice versa. The overall performance of the MIS is acceptable, and the system can be used as an alternate identification method for staphylococci.